2015
DOI: 10.1111/aos.12896
|View full text |Cite
|
Sign up to set email alerts
|

Role of vision loss, functional limitations and the supporting network in depression in a general population

Abstract: ABSTRACT.Purpose: Although the prevalence of depression in visually impaired older persons is high, the association between vision loss and depression seems to be influenced by factors other than visual impairment. In this study, the role of vision loss, functional limitations and social network characteristics in relation to depressive symptoms was investigated. Methods: Cross-sectional data (N = 1237) from the Longitudinal Aging Study Amsterdam were used to investigate the prevalence of depression (Center of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 47 publications
2
49
0
Order By: Relevance
“…Studies show that one‐third of older adults with vision impairment in general and age‐related eye disease such as age‐related macular degeneration and glaucoma, experience symptoms of depression and/or anxiety. This is twice as high as the prevalence found in the general elderly population .…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that one‐third of older adults with vision impairment in general and age‐related eye disease such as age‐related macular degeneration and glaucoma, experience symptoms of depression and/or anxiety. This is twice as high as the prevalence found in the general elderly population .…”
Section: Introductionmentioning
confidence: 99%
“…Vision loss is mainly a problem in older adulthood and is known to compromise quality of life (Langelaan et al 2007;Lamoureux et al 2009). Visually impaired elderly are at risk of specific detrimental health outcomes such as depression (van der Aa et al 2015;van Nispen et al 2016), anxiety (van der Aa et al 2015), falls and bone fractures (de Boer et al 2004). Vision loss has been ranked third, behind arthritis and heart disease, amongst the most common chronic conditions that require older adults to have assistance with activities of daily living (Watson 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the multiple regression analyses indicated that depression was associated with subjective vision in the same way as in the model of objective vision; however, we did not find a relationship between subjective vision and loneliness. Visual impairment has a profound negative impact on daily life (Evans, Fletcher, and Wormald, 2007;Hayman et al, 2007) and affects depression (Bookwala and Lawson, 2011;Diniz-Filho et al,2016;Van Nispen et al, 2016). It became clear that visual function impacts centenarians' SWB in the model controlled by residential status.…”
Section: Relationship Between Vision Impairment and Subjective Well-bmentioning
confidence: 99%
“…Several studies have indicated that vision affects SWB among older adults (Crews, ; Horowitz, ; Jopp, Rott, and Oswald, ; O'Donnell, ). Poor vision is related to life satisfaction (Bourque et al , ; Reinhardt, ), subjective health (Femia, Zarit, and Johansson, ), and depression (Bookwala and Lawson, ; Diniz‐Filho et al , ; Van Nispen et al , ). Visual function also impacts social activity, which promotes SWB among oldest‐old adults.…”
mentioning
confidence: 99%
See 1 more Smart Citation